Investigation of effect of ceramic material over which platinum coated piston crown and alcohols mixed with vegetable oils and its performance evaluation in Twin cylinder CRDI diesel engine. (2021) - Manjunatha, K.; Yerrennagoudaru, Hiregoudar; Prakash, KG.; Bhat, Suhas; Khan, Shadab; Saifuddin, Mohammed
Highlights: It is planned to custom blended alternative energy in the CI engine. Aldehydes, NOx, HC, CO2, in the finish gases are planned to lower during the engine itself. To learn the performance of the use blended alternative fuel in the CI engine. To analyze the finish gas. Abstract: The present paper focuses mainly on the use of biofuel mixed with alcohol in conventional and modified piston and the CI engine facilitated with common rail direct injection (CRDI Engine) was investigated powered different biofuels mixed with ethanol and methanol in terms of performance and emission characteristics. The results obtained from the experimentation showed that the best apricot oil mixed with ethanol and Pongamia oil mixed with methanol in modified piston for higher brake thermal efficiency (BTE) with less emissions for the fuel combinations of 50% biofuel mixed with 50% ethanol and methanol utilized in the investigations.